Improvement the system of state regulation the housing market by cost engineering - Shaposhnikova, I. (Ways to Improve Construction Efficiency, 2018)
The article proposes a methodology for improving the system of state regulation of the primary residential real estate market. It should be based on the creation of a special structure - state engineering monitoring of the cost of housing. It was determined that the creation of a state register of new buildings will solve the following problems: the opacity of the functioning of the housing market and the low efficiency of implemented state housing programs. This will improve the investment attractiveness of the housing industry. It is noted that the functioning of this registry should be based on the creation of an appropriate structure to provide objective information about new buildings in the country using the concept of virtual space. It is recognized that a multi-agent system should be used as the basis for software implementation and coordination of the processes of the proposed structure. It is proposed to introduce the following structural levels of the organization for selection in the register of new buildings: analytical and informational, informational and communicative, technical. This structure introduces a mechanism for managing information about new buildings through monitoring, analysis, planning and data control. This will allow all participants in the primary housing market to analyze, manage and share the risks inherent in this market. Cost engineering will be the basis for the implementation by local authorities of effective measures aimed at supporting the dynamic development of housing construction, increasing the volume of construction and investment in the construction industry, as well as increasing the volume of housing sales under state programs. The expected effect of the organization of this engineering center is the ability of investors to search for residential properties that can participate in government housing programs. Determining analytically the optimal cost of housing sales will allow developers to quickly respond to changes in market conditions. In addition, the timely detection of errors will allow the state to reduce its financial risks and improve the effectiveness of residential investment policy.